Diagnóstico de los niveles de estrés laboral como factor de riesgo psicosocial en la entidad Scotiabank Colpatria de Bogotá, sede torre B (2022)
The study of a diagnosis of work stress levels is of great importance at a national and international level due to the negative effects that it contracts and that they generate to the health of people and with it to organizations. The objective of this research is to analyze the causes and effects of the existence of work stress in the Scotiabank Colpatria entity, based on the application of a descriptive study method, through a survey with information of qualitative and quantitative questions, for this it is analyzed in first gender, age, profession, time in the company and time in the position and for the second instance a series of questions focused on working conditions as possible causes and effects of work stress and finally knowing the positive and negative aspects of work, according to feedback from respondents. Finally, and taking into account the